"Plan de mejora del esquema de compensación variable de la empresa Compunet S.A. Caso de estudio: COMPUNET S.A." (2023)
The present research aims to analyze the issue faced by Compunet S.A., a telecommunications company, where the variable compensation schemes are unsatisfactory for account managers, negatively impacting productivity and sales goals. To address this problem, a descriptive method was used, involving interviews with 13 active account managers.